The influence of culture time and the concentration of nitrogen in the medium on lipid content and fatty acid composition of microalgae (Experimental biology, 2016)
Microalgae are an enormous biological resource. They are used in different fields of science and technology. Recently there is an increasing interest in lipids and polyunsaturated fatty acids of microalgae, because they have more advantages compared to plant-derived raw material and seafood. Polyunsaturated fatty acids included in the lipid composition have special value for human health. They find wide application in medicine, pharmaceutics, cosmetology, food and other areas of human activity. Polyunsaturated fatty acids are essential for growth of the organism and play an important role in the prevention and treatment of many immune, inflammatory and cardiovascular diseases, such as rheumatoid arthritis, coronary heart disease, and cancer.       One of the biotechnological techniques to increase the content of lipids and polyunsaturated fatty acids in the biomass of microalgae is the optimization of their culture conditions. The most commonly used methods are the collection of biomass for the separation of lipids in the stationary phase of cell growth and limiting the nitrogen source on the environment of cultivation.      The object of the research was microalgae from the collection of the laboratory: green algae - Dictyochlorella globosa, diatom - Pleurosigma sp., characterized by the results of previous studies on the stable growth in the laboratory, also high content of lipids.       In this study used methods of accumulative cultivation of microalgae, extraction of lipids were performed according to the methods of Kates and Garbus, gravimetric method for the determination of total lipids, gas chromatography for fatty acid analysis.       In the work were studied the influence of time of cultivation and different concentrations of nitrogen on the accumulation of lipids and polyunsaturated fatty acids of green microalgae Dictyochlorella globosa and diatom microalgae Pleurosigma sp. It is established that optimal for the synthesis of lipids and acid conditions for microalgae Dictyochlorella globosa to use the Fitzgerald medium with normal nitrogen content within 10 days, and for Pleurosigma sp. to use the Fitzgerald medium with twice reduced content of nitrogen within 5 days. On the basis of obtained data we can conclude that for two promising microalgae Dictyochlorella globosa and Pleurosigma sp. defined culturing conditions that increase the content of lipids and polyunsaturated fatty acids. The results can be applied to develop the technology of obtaining high-efficiency microalgal bio-drugs of lipids and polyunsaturated fatty acids, which are promising for use in the treatment of atherosclerosis, of cardiovascular, cancer, inflammatory and other diseases.
Keywords: microalgae; lipids; polyunsaturated fatty acids; time of cultivation; the concentration of nitrogen.